Neurofibromatosis type 1: results of our own study (Republic of Bashkortostan) - R. N. Mustafin; M. A. Bermisheva; R. R. Valiev; E. E. Khusnutdinova (Успехи молекулярной онкологии)
Introduction. Neurofibromatosis type 1 (NF1) is the most common hereditary tumor syndrome (frequency of its occurrence in the world is 1 : 3000 of the population). The main clinical manifestations of the disease are multiple café-au-lait macules on the skin and neurofibromas, skeletal abnormalities and cognitive deficits. The disease is based on mutations in the oncosuppressor gene NF1. This disease is characterized by significant clinical polymorphism of manifestations, even among members of the same family. No geno-phenotypic correlations were found for NF1. Therefore, it is assumed that modifier genes are the cause of the varying expressiveness of the disease. Materials and methods. Clinical-epidemiological and molecular-genetic research of patients with NF1 in the Republic of Bashkortostan (RB) was carried out. Sequencing was used to search for intragenic mutations in 57 exons of the NF1 gene. Microsatellite analysis was used to detect the deletion of the entire gene.Results. The frequency of occurrence of NF1 in RB was 1 : 10153 of the population. Analysis of the clinical manifestations of NF1 in RB patients showed a lower incidence of brain cysts in patients born in mixed marriages, which indicates the protective role of mestization. In patients with NF1 who inherited the disease from the mother, a more frequent development of skeletal anomalies and facial dysmorphism was determined. We identified 1 deletion of the entire NF1 gene in 1 patient and 14 intragenic mutations (c.205-1G>C, с.1278G>A, c.1369_1370insGGGTC, с.1570G>A, с.1973_1974delTC, c.2806A>T, с.2991-1G>C, c.3158C>G, с.3526_3528delAGA, с.3826delC, с.4514+5G>A, с.4537С>Т, c.5758_5761delTTGA, с.6792С>A) in 20 patients with NF1. We determined the random distribution of the types of mutations and did not reveal the specific features of the NF1 clinic depending on the type of mutations.Conclusions. The protective role of crossbreeding in relation to brain cysts, as well as the predominance of skeletal anomalies in patients with NF1 inheritance from the mother, indicate the role of modifier genes in the pathogenesis of the disease. The identified mutations in the NF1 gene will allow us to perform prenatal prevention of NF1 in RB patients.